Examining the influence of Social Media Marketing on Consumer's Online Purchasing Decisions: A comparative study of consumers in Nepal and Finland. - Thapa Shrees Magar, Khuma; Chalise, Smita (My University, 2026)
ABSTRACT : Social media marketing is an interactive web that allows buyers and sellers to communicate, exchange feedback, and to stay updated on the current market trends. This study investigates the influence of SMM features and consumer features on consumers’ online purchase decisions. The primary objective of this thesis is to explore the impact of social media marketing (SMM) on consumers’ online purchase decisions in Nepal and Finland. In this thesis, the independent variables are divided into two main categories: social media marketing features and consumer features. The social media features include informativeness, perceived relevance, interactivity, and eWOM. While consumer features include attitude, trust, perceived security, and price sensitivity. All these independent variables were used to analyze the influence on consumers’ online purchases in Nepal and Finland. The study used purposive sampling, which is a non-probability sampling technique. A deductive research approach has been used in the study. In this research, primary survey data were collected from consumers in Finland and Nepal by using Webropol. The study consists of a total of 202 respondents, with 92 respondents from Finland and 110 respondents from Nepal. Data was analysed using IBM SPSS Statistics software. In this study, different data analysis methods were used, such as descriptive statistics, Confirmatory factor analysis, and multiple regression analysis to test the hypothesis. The findings reveal that female consumers of the young age group are more active in using SM Platforms and are more involved in online purchasing than male consumers in both countries. Out of all eight independent variables, only the independent variable attitude was found to have a statistically significant effect on consumers’ online purchasing decisions both in Finland and Nepal. Similarly, Nepali consumers' online purchasing decisions are influenced by eWOM and price sensitivity, as it shows a positive and significant relationship, whereas trust in sellers significantly influenced the Finnish consumers’ online purchase decisions, as it shows a positive and significant relationship. Therefore, although social media marketing features have an influence on consumer online purchase, consumer features are seen to have a greater influence on consumer online purchase decisions. Finally, it is concluded that Nepali consumers online purchase decision is influenced by attitude, eWOM, and price sensitivity, whereas Finnish consumers online purchase decisions are influenced by attitude and trust, which reflects the difference in consumer online purchase decisions in both countries.
Keywords: social media; online advertising; consumer behaviour; electronic business; trust; interactivity; Internet; consumers; marketing; purchasing; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business